Effect of postoperative high load long duration inspiratory muscle training on pulmonary function and functional capacity after mitral valve replacement surgery: A randomized controlled trial with follow-up. - Fatma A Hegazy (Public Library of Science (PLoS), 2021)
Objectives Although, pre-operative inspiratory muscle training has been investigated and reported to be an effective strategy to reduce postoperative pulmonary complications, the efficacy of postoperative inspiratory muscle training as well as the proper load, frequency, and duration necessary to reduce the postoperative pulmonary complications has not been fully investigated. This study was designed to investigate the effect of postoperative high-load long-duration inspiratory muscle training on pulmonary function, inspiratory muscle strength, and functional capacity after mitral valve replacement surgeries. Design Prospective randomized controlled trial. Methods A total of one hundred patients (mean age 38.3±3.29years) underwent mitral valve replacement surgery were randomized into experimental (n = 50) and control (n = 50) groups. The control group received conventional physiotherapy care, while experimental group received conventional care in addition to inspiratory muscle training, with 40% of the baseline maximal inspiratory pressure targeting a load of 80% by the end of the 8 weeks intervention protocol. Inspiratory muscle training started on the patient's first day in the inpatient ward. Lung functions, inspiratory muscle strength, and functional capacity were evaluated using a computer-based spirometry system, maximal inspiratory pressure measurement and 6MWT respectively at 5 time points and a follow-up assessment was performed 6 months after surgery. Repeated measure ANOVA and post-hoc analyses were used (p <0.05). Results Group-time interactions were detected for all the studied variables (p<0.001). Between-group analysis revealed statistically significant postoperative improvements in all studied variables in the experimental group compared to the control group (p <0.001) with large effect size of η2 ˃0.14. Within-group analysis indicated substantial improvements in lung function, inspiratory pressure and functional capacity in the experimental group (p <0.05) over time, and these improvements were maintained at follow-up. Conclusion High intensity, long-duration postoperative inspiratory muscle training is highly effective in improving lung function, inspiratory muscle strength, and functional capacity after mitral valve replacement surgeries.